2-Cyanoanilinium nitrate - Li-Jing Cui; Xiao-Chun Wen (Acta Crystallographica Section E, 2008)
In the title compound, C7H7N2+·NO3−, all atoms of the cation, with the exception of two H atoms of the NH3 group, lie on a mirror plane, while the anion lies across this plane with the N and one O atom on the mirror plane. In the crystal structure, the organic cations and NO3− anions are linked by N—H...N and N—H...O hydrogen bonds, forming a two-dimensional network parallel to (100).